FATOR DE COBERTURA E MANEJO DA USLE/RUSLE PARA A CULTURA DO MILHO NO CERRADO BRASILEIRO - NASCIMENTO, Maryanne Ramos; MONTEIRO, Felipe das Neves; PANACHUKI, Elói; SIMÕES, Mayara dos Santos; SANTANA, Carla Fernandes (ANAIS DO ENIC, 2023)
.